Virtual tour of East African Drylands - Big Lands, Big Opportunities - International Livestock Research Institute (International Livestock Research Institute, 2021)
Take a virtual trip to the great savanna lands of East Africa—cradle of humankind, home to traditional nomadic pastoralists, and last refuge of some of the most spectacular wildlife populations on earth. Learn about the productivity and resilience of these mostly under-appreciated and often ignored landscapes. This video was originally created for the Global Landscapes Forum on Drylands 3-4 June 2021.